Peptide Antibodies Methods and Protocols - Houen, Gunnar.; Houen, Gunnar. (Methods in Molecular Biology,, 2015)
This extensive volume covers basic and advanced aspects of peptide antibody production, characterization, and uses. Although peptide antibodies have been available for many years, they continue to be a field of active research and method development. For example, peptide antibodies which are dependent on specific posttranslational modifications are of great interest, such as phosphorylation, citrullination, and others, while different forms of recombinant peptide antibodies are gaining interest, notably nanobodies, single chain antibodies, TCR-like antibodies, among others. Within this volume, those areas are covered, as well as several technical and scientific advances: solid phase peptide synthesis, peptide carrier conjugation and immunization, genomics, transcriptomics, proteomics and elucidation of the molecular basis of antigen presentation and recognition by dendritic cells, macrophages, B cells and T cells. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Comprehensive and authoritative, Peptide Antibodies: Methods and Protocols serves as an ideal reference for researchers exploring this vital and expansive area of study.